Additions To Crimean Fauna Of Water Beetles (Coleoptera: Dytiscidae, Hydrophilidae) - Czesław Greń (Zenodo, 2018)
The paper presents new records for five species of water beetles from the Crimean peninsula: Agabus ( Agabus ) fulvaster Zaitsev, Berosus ( Enoplurus ) fulvus Kuwert, Cercyon ( Cercyon ) tristis (Illiger), Enochrus ( Lumetus ) ater (Kuwert) and Limnoxenus niger (Gmelin). Three of them are simultaneously new to the fauna of Ukraine. The number of species from the family Dytiscidae known from the Crimea is currently 63, and the family of Hydrophilidae 62. : {"references": ["Bilyashiwsky M.M. 1993. K poznaniyu fauny zhukov-plavuntsov (Coleoptera, Dytiscidae) Kryma. (A contribution to the dytiscid-beetle fauna (Coleoptera, Dytiscidae) of the Crimea). Journal of the Ukrainian Entomological Society 1(1): 15\u201318.", "Boukal D.S., Boukal M., Fik\u00e1\u010dek M., H\u00e1jek J., Kle\u010dka J., Skalick\u00fd S., \u0143\u0165astn\u00fd J., Tr\u00e1vn\u00ed\u010dek D. 2007. Catalogue of water beetles of the Czech Republic (Coleoptera: Sphaeriusidae, Gyrinidae, Haliplidae, Noteridae, Hygrobiidae, Dytiscidae, Helophoridae, Georissidae, Hydrochidae, Spercheidae, Hydrophilidae, Hydraenidae, Scirtidae, Elmidae, Dryopidae, Limnichidae, Heteroceridae, Psephenidae). Klapalekiana 43(Suppl.): 1\u2013289.", "Fery H. 2009. New species of the Hydroporus longulus-group from Iran, Armenia and Turkey with a synopsis of the group (Coleoptera: Dytiscidae). Acta Entomologica Musei Nationalis Pragae 49(2): 529\u2013558.", "Gramma V.M. 1998. New for the Crimea species of water beetles (Coleoptera: Haliplidae, Dytiscidae). Izvestiya Kharkovskogo Entomologicheskogo Obshchestva 6(2): 41\u201342.", "Gre\u0144 C., Lubecki K. 2018. Water beetles (Coleoptera: Adephaga, Hydrophiloidea, Byrrhoidea) in Bulgaria: new records. Annals of the Upper Silesian Museum in Bytom, Entomology 26(007): 61\u201380. DOI: http://doi.org/10.5281/zenodo.1184328", "Hansen M. 1987. The Hydrophiloidea (Coleoptera) of Fennoscandia and Denmark. Fauna Entomologica Scandinavica 18: 1\u2013254.", "Lindeman K.E. 1871. Review of geographical distribution beetles of Russian empire, introduction, the foreword, Northern, Moscow and Turkestani provinces. Trudy Russkogo Entomologicheskogo Obshchestva 6(1): 41\u2013366 [in Russian].", "Fik\u00e1\u010dek M., Angus R.B., Gentili E., Jia F., Minoshima Y.N., Prokin A., Przewo\u017any M., Ryndevich S.K. 2015. Family Hydrophilidae, pp. 37\u201376, In: L\u00f6bl I. & L\u00f6bl D. (Eds.), Catalogue of Palaearctic Coleoptera. Vol. 2/1. Hydrophiloidea \u2013 Staphilinoidea. Revised and updated edition. Brill, Leiden-Boston.", "Nilsson A.N. 2003. Dytiscidae, pp. 35\u201378, In: L\u00f6bl I., & Smetana A. (Eds.), Calalogue of Palaearctic Coleoptera, Vol. 1. Apollo Books, Stenstrup.", "Ribera I., Sch\u00f6dl S., Hernando C. 1997. Enochrus ater (Kuwert) and E. salomonis (Sahlberg) (Coleoptera: Hydrophilidae), two widespread but overlooked species new to the European fauna. Hydrobiologia 354: 183\u2013188.", "Ryndevich S.K. 2007. Beetles of superfamily Hydrophiloidea (Coleoptera: Helophoridae, Hydrochidae, Spercheidae, Hydrophilidae) of the Crimean peninsula. Russian Entomological Journal 16(3): 267\u2013273.", "Ryndevich S.K. 2013. Zoogeographic structure of Hydrophiloid beetles fauna (Coleoptera: Hydrophiloidea) of Palearctic subtaiga. Hydroentomology in Russia and adjacent countries: Materials of the Fifth All-Russia Symposium on Amphibiotic and Aquatic Insects / Papanin Institute for Biology of Inland Waters, Russian Academy of Sciences. \u2013 Yaroslavl: Filigran: 145\u2013156.", "Ryndevich S.K., Fik\u00e1\u010dek M. 2013. Faunistic and Zoogeographic Notes on Hydrophiloid Beetles from the Palaearctic Region (Coleoptera: Hydrophilidae). Vestnik BarDU Seriya Biologicheskiye Nauki Selskokhozyaistvennye Nauki 1: 32-37.", "Sch\u00f6dl S. 1991. Revision der Gattung Berosus Leach. 1. Teil: Die pal\u00e4arktischen Arten der Untergattung Enoplurus (Coleoptera: Hydrophilidae). Koleopterologische Rundschau 61: 111\u2013135.", "Zaytsev F.A. 1908. To fauna of water beetles of the Crimea and Taman. Ezhegodnik Zoologicheskogo Muzeya AN 13: 1\u20138 [in Russian].", "Zaytsev F.A. 1972. Fauna of the USSR. Coleoptera. Families: Amphizoidae, Hygrobiidae, Haliplidae, Dytiscidae, Gyrinidae. Israel Program for Scientific Translations, Jerusalem: 401 pp."]}